PERFORMANCE EVALUATION OF ROUTING PROTOCOLS IN MANETS - YAHAYA, A. U.; A. J. KAWU; M. S. TABRA; M. K. AHMED (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2020)
Mobile Adhoc Network (MANET) is a decentralized independent wireless system that is selfconfigured with a collection of mobile communication node that moves randomly. Challenges such as routing, power management, frequent topology changes, and security are faced by network developers and designers. Routing is one of the core factors that have great influence on network performance, its discovery and maintenance are critical issues. Several studies have been done on the performance evaluation of routing protocols using different evaluation methods. In this paper, we evaluated the performance of DSR, OLSR and GRP, a proactive, reactive and hybrid Adhoc routing protocols respectively using OPNET Modeler Simulator. The performance of these routing protocols is analyzed by Delay, Throughput, Network load, Retransmission Attempts and Data Dropped. The comparison analysis has been carried out about these protocols, simulation results shows that OLSR outperformed both GRP and DSR routing protocols.